Peran Etika Bisnis dalam Moderasi Pengaruh Penerapan PPN terhadap Kinerja Keuangan Perusahaan B2B - Wibawa, Herry Wira; Dewi Nari Ratih Permada (Jurnal Ilmiah Ekonomi, Akuntansi, dan Pajak, 2025)
This study investigates the relationship between business ethics and VAT implementation with the aim of assessing the combined effect of both on the financial performance of B2B companies. The main theories underlying this study are the Ability to Pay Theory, Stakeholder Theory, and Ratio Analysis Theory. The study uses a positive research philosophy approach and a quantitative case study design with a structured questionnaire involving 30 respondents from PT Bhinneka Mentari Dimensi or Bhinneka.Com, the oldest B2B e-Commerce company in Indonesia. Data analysis was conducted using SPSS using descriptive and inferential statistics. The results show that VAT implementation indirectly affects financial performance through business morality. This mediating role is associated with stakeholder theory and the ability to pay. The low direct effect of VAT is related to an efficient company structure, company size, and reliance on self-reported data. B2B companies should embed business ethics principles in their operations, with management implementing a framework to ensure accountability in tax reporting and practices. The originality of this study contributes to the literature by emphasizing the distinctive role of business ethics as a bridge in the relationship between VAT implementation and financial performance of B2B companies, shifting attention from general tax compliance to specific VAT mechanisms and incorporating ethical dimensions in financial analysis.